2013
DOI: 10.3892/ijo.2013.1853
|View full text |Cite
|
Sign up to set email alerts
|

cAMP signalling inhibits p53 acetylation and apoptosis via HDAC and SIRT deacetylases

Abstract: Abstract. Activation of cAMP signalling potently inhibits DNA damage-induced apoptosis in acute lymphoblastic leukemia cells by promoting the turnover of p53 protein. Recently, we showed that the cAMP-induced destabilization of p53 in DNA-damaged cells occurs as a result of enhanced interaction between p53 and HDM2. In this report, we present results showing that increased levels of cAMP in cells with DNA damage enhances the deacetylation of p53, an event that facilitates the interaction of p53 with HDM2, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…According to previous studies, HDAC inhibitors are also reported to induce acetylation in non-histone proteins ( 31 ). For example, the HDAC1 inhibitor TSA leads to acetylation of p53 on K373 primarily under conditions in which cells are subjected to ionizing radiation, acting as a transcription factor regulating multiple genes important for the regulation of cell cycle arrest, senescence and apoptosis ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, HDAC inhibitors are also reported to induce acetylation in non-histone proteins ( 31 ). For example, the HDAC1 inhibitor TSA leads to acetylation of p53 on K373 primarily under conditions in which cells are subjected to ionizing radiation, acting as a transcription factor regulating multiple genes important for the regulation of cell cycle arrest, senescence and apoptosis ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of NF-κB plays a central role in inflammation and exerts multiple effects in various cellular responses [ 72 ]. Several studies have demonstrated that resveratrol regulates the activity of apoptotic transcription factors and regulates inflammatory responses by modulating NF-κB [ 73 , 74 , 75 ]. Taken together, our data indicate that resveratrol may inhibit neuronal inflammatory responses by suppressing the activation of NF-κB in microglia under ischemic brain injury.…”
Section: Resultsmentioning
confidence: 99%
“…This finding also implies that drugs targeting the cAMP signaling pathway could be possibly used to modulate radiation-induced apoptosis, thereby increasing the radiosensitivity of cancer cells or protecting normal cells from radiation. The cAMP signaling system can stimulate or inhibit apoptosis depending on cell types [ 27 ] through diverse molecular mechanisms involving Bcl-2 family proteins, p53, and histone deacetylase [ 16 , 28 , 29 ]. Thus, this study presents a novel mechanism for the cAMP signaling system to regulate cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the cAMP signaling system was found to inhibit the repair of γ-ray-induced DNA damage by promoting degradation of the XRCC1 protein in human lung cancer cells [ 15 ]. The cAMP signaling system was also reported to inhibit DNA-damage induced apoptosis of leukemia cells by promoting acetylation and turnover of p53 [ 16 , 17 ]. Thus, we hypothesized that the cAMP signaling system might be involved in the regulation of ATM activation, the key event triggering signaling pathways in response to DNA damage.…”
Section: Introductionmentioning
confidence: 99%